Dietary and Exercise Interventions for Perimenopausal Women: A Health Status Impact Study - Hao, Shuping; Tan, Sisi; Li, Jing; Li, Weimin; Li, Jingyun; Cai, Xiaochen; Hong, Zhongxin (Frontiers in Nutrition, 2022)
Purpose: Our aim is to explore the impact of different intervention methods on the diet and exercise behavior and physical health indicators of perimenopausal women. Methods: 78 perimenopausal women divided into three groups. Group A received routine gynecological diagnosis and treatment and participated in centralized lifestyle health education. Group B required to participate in all intensive education content, professional dietitians to give individualized dietary guidance. Group C received intensive education, individualized diet intervention, and intensified resistance exercise. Dietary scores, exercise habits, waist circumference, body mass index, fat and muscle mass were observed after 3 months. Results: After intervention, the total diet score of group C was higher than that of group A and B, and the red meat score was significantly reduced. The number of patients in group B and group C who exercised >3 times per week and the number of resistance exercises per week were significantly increased, while the number of aerobic exercises per week in group C was significantly increased. The body fat and waist circumference were significantly reduced, and skeletal muscle weight was significantly increased; body mass index, trunk fat ratio and waist to hip ratio were significantly decreased in group B and C, while trunk muscle was significantly increased in group C. Conclusion: The combined intervention of the three methods can give full play to the synergistic effect of various interventions, and the improvement effect of increasing the appropriate amount of resistance exercise is more obvious, which is worthy of further promotion and application.